Pengembangan Kesadaran Keberagamaan dan Pembentukan Karakter Siswa Melalui Pembiasaan Shalat Dhuha’ - Yudabangsa, Adrian (Attractive : Innovative Education Journal, 2020)
Religious awareness and the formation of student character was an embodiment results of studying and habituation implemented by students, either at home, school or environment. When students at school were very limited time, habituation should be maximized as optimal as possible. One of the habits that brings positive change for students was praying Duha. This article developing religious awareness and gaining students’ character through the habituation of praying Duha. This research was qualitative method which obtained data from observation and interviews. The results of this study indicate an increase and positive change during the students performing the Dhuha prayer. These changes occur in aspects of religious awareness, character, intelligence and character of students. Key words: Religious Awareness, Education Character, Praying Duha’